Vitamin B2 - sensitized photooxidation of dopamine - Massad, Walter Alfredo (2008)
Kinetics and mechanism of the photo-oxidation of the natural catecholamine-type neurotransmitter dopamine (DA) has been studied in aqueous solution, under aerobic conditions, in the presence of riboflavin (Rf, vitamin B2) as a photosensitizer. Results indicate the formation of a weak dark complex Rf–DA, with a mean apparent association constant Kass = 30 M)1 , only detectable at DA concentrations much higher than those employed in photochemical experiments. An intricate mechanism of competitive reactions operates upon photoirradiation. DA quenches excited singlet and triplet states of Rf, with rate constants of 4.2 · 109 and 2.2 · 109 M)1 s )1 , respectively. With the catecholamine in a concentration similar to that of dissolved molecular oxygen in air-saturated water, DA and oxygen competitively quench the triplet excited state of Rf, generating superoxide radical anion (O2 •) ) and singlet molecular oxygen (O2( 1 Dg)) by processes initiated by electron and energy-transfer mechanisms, respectively. Rate constants values of 1.9 · 108 and 6.6 · 106 M)1 s )1 have been obtained for the overall and reactive (chemical) interaction of DA with O2( 1 Dg). The presence of superoxide dismutase increases both the observed rates of aerobic DA photo-oxidation and oxygen uptake, due to its known catalytic scavenging of O2 •) , a species that could revert the overall photo-oxidation effect, according to the proposed reaction mechanism. As in most of the catecholamine oxidative processes described in the literature, aminochrome is the DA oxidation product upon visible light irradiation in the presence of Rf. It is generated with a quantum yield of 0.05.